Mechanism and effects of STING–IFN-I pathway on nociception: A narrative review - Yang, Jinghan; Ding, Hui; Shuai, Bo; Zhang, Yan; Zhang, Yan (Frontiers in Molecular Neuroscience, 2023)
Since the discovery of STING in 2008, numerous studies have investigated its functions in immunity, inflammation, and cancer. STING activates downstream molecules, including IFN-I, NLRP3, and NF-κB. STING–IFN-I pathway plays a vital role in nociception. After receiving the upstream signal, STING is activated and induces the expression of IFN-I, and after paracrine and autocrine signaling, IFN-I binds to IFN receptors. Subsequently, the activity of ion channels is inhibited by TYK2, which induces an acute antinociceptive effect. JAK activates the PIK3 and MAPK-MNK-eIF4E pathways, which sensitizes the nociceptors in the peripheral nervous system. In the mid-late stage, the STING-IFN-I pathway activates STAT, increases proinflammatory and anti-inflammatory cytokines, inhibits ER-phagy, and promotes microglial M1-polarization in the central nervous system, leading to central sensitization. Thus, the STING-IFN-I pathway may exert complex effects on nociception at various stages, and these effects require further comprehensive elucidation. Therefore, in this review, we systematically summarized the mechanisms of the STING-IFN-I pathway and discussed its function in nociception.